Analysis of spatial and environmental justice in three Mexican cities - Araujo-Alvarado L; Ortega-Montoya CY; Ávila-Galarza A (MATEC Web of Conferences, 2019)
The accelerated growth of cities in developing countries poses a challenge for urban planning such as guaranteeing the safety of all inhabitants from natural and anthropogenic threats. The objective of this study is to determine the urban areas and social sectors of three medium sized Mexican cities that are exposed to high risk activities. The results indicate that for the metropolitan area of San Luis Potosi, 57.6% of high risk activities are within the urban sprawl, while 100% are in the cities of Zacatecas and Fresnillo. In all three case studies, most of the activities studied are in areas with low and medium rates of marginalization. In San Luis Potosi, 4.1% are in areas with high and very high population density but none of the case studies showed a conglomeration of these types of risks in a determined area of the cities. A database of companies with high risk activities, regulated at a federal level, public became public in Mexico in 2014. This information is of great value at a local level to define the strategies of land use planning that guarantee access to environmental justice as well as effective prevention strategies and responses to chemical emergencies.